Beneficial Effects of Limosilactobacillus fermentum CECT 5716 Administration to Infants Delivered by Cesarean Section - Blanco-Rojo, Ruth; Maldonado, José; Schaubeck, Monika; Özen, Metehan; López-Huertas, Eduardo; Olivares, Mónica (Frontiers in Pediatrics, 2022)
Cesarean section (CS) disrupts the natural microbiota colonization process in infants, which might compromise immune system maturation, leading to a higher risk of infections. We evaluated the effect of the probiotic Limosilactobacillus (L.) fermentum CECT 5716 on the incidence of gastrointestinal and respiratory infections in the CS infant subgroups (n=173) of three randomized clinical trials in which this probiotic strain was demonstrated to be proved safe and effective for preventing infections. Therefore, the data for the CS infants were extracted to obtain the incidence rate ratio (IRR) and 95% CI for gastrointestinal and respiratory infections for each study and were then combined to obtain a pooled IRR and 95% CI using the generic inverse variance method. There was a significant reduction of 73% in the incidence of gastrointestinal infections in CS infants receiving L. fermentum CECT5716 compared with those receiving the control formula (n = 173, IRR: 0.27 [0.13, 0.53], p = 0.0002). Regarding respiratory infections, although pooled results showed a reduction of 14% in the probiotic group, the difference was not statistically significant (n = 173, IRR [95% CI]: 0.86 [0.67, 1.11], p= 0.25). In conclusion, the administration of L. fermentum CECT 5716 to CS-born infants protects them from gastrointestinal infections by reducing the risk by up to 73% in this population